Development and Fabrication of Zavegepant Loaded Mucoadhesive Microemulsion for Intranasal Delivery - Akshay Vikhe; Godge, Rahul K.; Shinde, Ganesh S.; Vikhe, Dattaprasad N.; Mhaske, Shubham B. (Kurdistan Journal of Applied Research, 2026)
To develop and optimize zavegepant-loaded mucoadhesive microemulsions for intranasal delivery, utilizing quality-by-design principles for enhanced bioavailability and rapid onset in acute migraine management. Zavegepant-loaded microemulsions were formulated using Labrafil M 1944 CS (oil), Brij 35 (surfactant), polyethylene glycol (PEG) 400 (co-surfactant), gellan gum (mucoadhesive polymer), and double distilled water. A central composite design with 4 factors (oil, surfactant, co-surfactant, and water concentrations) was employed to optimize critical quality attributes including globule size, zeta potential, and polydispersity index. Comprehensive characterization included particle size analysis, surface charge determination, drug content, permeation studies, and accelerated stability testing. Twenty-seven formulations were evaluated, with statistical analysis identifying concentration as the primary determinant of microemulsion properties (F-values: 144.64-375.27). Optimization yielded formulation (10% Labrafil M 1944 CS, 52% Brij 35, 18% PEG 400, 20% water) with ideal characteristics: globule size 58.7 nm, Polydispersity index 0.142, zeta potential -12.7± mV, and drug content 99.6. It demonstrated superior ex-vivo drug permeation (91.7% at 12h) and remained stable for 6 months under accelerated conditions. The optimized mucoadhesive microemulsion showed good in vitro results with fast drug release, strong permeation, and stable performance. This suggests it could be a useful intranasal system for zavegepant in treating migraines, but in vivo studies are still needed to confirm its clinical use.